Morphometric analysis of dry acetabulum and iliac bones from anatomy museums in south eastern Nigeria with relation to clinical practice - Ekwedigwe, Henry Chinedum; Esom, Emmanuel; Katchy, Amechi Uchenna; Anyaehie, Udo Ego; Ozor, Ignatius Ikem; Ekwunife, Remigius Tochukwu; Aniagu, Chikaodi Victoria (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Good outcomes of total hip replacement and acetabular surgeries have been linked to proper understanding of the morphometry of acetabular and iliac bones. The aim of this study was to analyze the clinical morphometry of dry acetabulum and iliac bones in southeastern Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The measurements were done on human hip bones in anatomy museums using a Vernier caliper. The acetabular and iliac bone parts were measured. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. A total of 148 dry hip bones were measured during the study. The mean acetabular depth and diameter are 32.10±2.33 mm, and 53.93±2.74 mm respectively. The mean thicknesses of the acetabular walls are 5.88±1.38 mm, 12.64±1.84 mm, 15.79±2.07 mm and 19.74±2.18 mm for the antero-inferior, antero-superior, postero-inferior and postero-superior walls respectively. The distances between landmarks on the iliac bone are: anterior-inferior-iliac-spine – posterior-inferior-iliac-spine = 112.91±8.01 mm, posterior-superior-iliac-spine – anterior-inferior-iliac-spine = 135.29±8.04 mm, anterior-inferior-iliac-spine – anterior-superior-iliac-spine = 34.98±9.55 mm, posterior-superior-iliac-spine – upper-edge-of-acetabulum = 119.14±7.83 mm and anterior-superior-iliac-spine – nearest-edge-of-acetabulum = 55.71±5.60 mm. The regression model for prediction of diameter of the acetabulum using the depth of the acetabulum shows that for every 1 mm increase in the acetabular depth, the acetabular diameter increases by 0.312 times. The regression equation is “Y = bx + a”; Y = acetabular diameter, x = acetabular depth, b = margin of error = 0.312, and a = constant determined to be 43.919. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The study established the mean values and the relationship between acetabular depth and diameter.